Is there a link between the physicochemical characteristics of multiwalled carbon nanotubes and their genotoxicity in human cells? - Louro, Henriqueta (2014)
The wide applicability of manufactured nanomaterials (NM) has led to an increased risk of human exposure and environmental dissemination. In particular, multi-walled carbon nanotubes (MWCNT) have been developed for industrial purposes, but the same properties that render these materials so attractive may also cause higher toxicity. However, contradictory results concerning their genotoxicity and carcinogenicity have been reported, suggesting that minor changes in physicochemical properties may determine their toxicity. The objective of this work was to characterize the cyto- and genotoxic effects of MWCNTs that differ in thickness, length and aspect ratio (NM-401, NM-402 and NM-403, JRC repository) in human-derived bronchial epithelial cells (BEAS-2B), in order to ascertain which characteristic(s) may be determinant for their genotoxicity. After NM dispersion using a standardized protocol, cell cultures were exposed to several NM concentrations (0-256 μg/ml). Cell viability was evaluated by the Trypan blue dye exclusion assay. For genotoxicty testing, a combination of the alkaline comet assay (3- or 24h- exposure) and the cytokinesis-blocked micronucleus assay (48h-exposure) was used. The results showed that NM-401 and NM-403 were cytotoxic following 24h exposure, whereas the highest doses of NM-402 were cytotoxic at 3h. The genotoxicity results in relation to the different MWCNT tested were not consistent, indicating that diameter and length are rather important properties that influence the genotoxic potential of these NM. In summary, our work confirmed that the standard genotoxicity tests can be applied for evaluating the genotoxicity of different types of MWCNT. However, we also concluded that specific physicochemical properties impact on the genotoxic potential of these high aspect ratio NM, an issue that has to be further understood, possibly by targeted testing. Regarding safety assessment and related regulatory aspects, the differential genotoxicity observed for closely related NM highlights the importance of investigating the toxic potential of each NM individually, instead of assuming a common mechanism and equal genotoxic effects for a set of similar NM.